Renewable Energy Jobs and Sector Skills Mapping for Pakistan - World Bank (Washington, DC, 2022)
The Government of Pakistan (GOP) has adopted ambitious national renewable energy (RE) targets under the RE policy 2019. The policy sets out a growth trajectory for grid connected, non-hydro renewables, mandating at least 20 percent renewables in the country’s installed power generation capacity by 2025 and 30 percent by 2030. The government has simultaneously approved a comprehensive power generation capacity expansion plan, the integrated generation capacity expansion plan 2021-2030. Since large hydropower makes up the bulk of capacity additions in the IGCEP, new wind, solar, and bagasse projects in the IGCEP account for approximately 11,700 MW compared to 16,300 MW of non-hydro RE needed to meet the national RE targets. To capitalize on the employment creation potential of the RE targets and the IGCEP, policy makers will have to anticipate changes in workforce trends and develop a preemptive plan to manage skill requirements and prevent workforce shortages. This study was commissioned by the World Bank to facilitate cohesive RE workforce planning and identify skill gaps that can inhibit RE investments in Pakistan. The findings of the study will help inform skill development in RE by providing policy makers and other stakeholders, including the higher education commission (HEC) and the national vocational and technical training commission (NAVTTC), with indicative employment projections required for long-term planning.